The effect of plant domestication on host control of the microbiota - Soldan, Riccardo; Fusi, Marco; Cardinale, Massimiliano; Daffonchio, Daniele; Preston, Gail M. (Communications biology, 2021)
Macroorganisms are colonized by microbial communities that exert important biological and ecological functions, the composition of which is subject to host control and has therefore been described as “an ecosystem on a leash”. However, domesticated organisms such as crop plants are subject to both artificial selection and natural selection exerted by the agricultural ecosystem. Here, we propose a framework for understanding how host control of the microbiota is influenced by domestication, in which a double leash acts from domesticator to host and host to microbes. We discuss how this framework applies to a plant compartment that has demonstrated remarkable phenotypic changes during domestication: the seed. Soldan and co-authors propose an evolutionary framework for understanding how host control of the microbiota is influenced by artificial selection. They go on to discuss the potential effect of domestication syndrome on the seed microbiome and plant-microbe interactions in the spermosphere.